A musicalização infantil no processo de construção do ser criança - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
This research has music and early childhood education as its theme, with the objective of describing the contributions of early childhood musicalization to children's development from the perspective of early childhood musicalization teachers from the Social Sementes Musicais Project, in Santarém – Pará. It was observed during the course of work that, when working with children, it is necessary to provide experiences that can be significant during their development process. Thus, musicalization allows activities to be carried out in a playful way, awakening children's pleasure in learning. In this sense, providing children with a good musical experience allows them to develop fully and become culturally enriched. This research is a case study developed in a children's musicalization class in the Musical Seeds Social Project, its theoretical basis is books, magazines, scientific journals and interviews, classified as exploratory and qualitative research, seeking to present the contributions that musicalization can provide to the process of integrating the child's social being, as well as giving new meaning to the importance of music as a playful pedagogical instrument and reflecting the importance of children's musicalization in the child's development.
Keywords: Educação infantil; Música - Instrução e estudo; Música na educação; Educação de crianças; CNPQ:: CIÊNCIAS HUMANAS